Conscious control in speech pathology and speech rehabilitation following stroke - Pastryk, Tetyana; Kotys, Olena; Dyachuk, Nataliia; Milinchuk, Volodymyr; Пастрик, Тетяна; Котис, Олена; Дячук, Наталія; Мілінчук, Володимир (Lesya Ukrainka Eastern European National University, 2019)
The article presents results of the research conducted in speech rehabilitation period of patients after stroke. The study aims to identify conscious control in speech rehabilitation period of the patients who were diagnosed to have Broca’s aphasia. A sample of 22 patients with Broca’s aphasia, or efferent motor aphasia (Luria, 2004) in the left hemisphere, who stayed at the Volyn Regional Clinical Hospital (Lutsk, Ukraine) during rehabilitation period, was approached through purposeful sampling method for this research. The non-laboratory measure of speech assessment was administered along with demographic data. Results showed that conscious control that usually remains in this group of people plays a crucial role in psychological intervention. The article also discusses the main neuropsycholinguistic principles that help to utilize the potential of conscious control in the process of speech rehabilitation of the patients after stroke.Статтю присвячено результатам мовленнєвої реабілітації пацієнтів після інсульту. Дослідження мало за мету встановити аспекти свідомого контролю під час мовленнєвої реабілітації осіб із афазією Брока, або моторної еферентної афазії (Лурія, 2004), лівої півкулі. Вибірку склали 22 пацієнти Волинської обласної клінічної лікарні в Луцьку (Україна) упродовж реабілітаційного періоду. Дослідження здійснено на основі методів цільового формування вибірки, а також застосування неапаратурного методу оцінки мовлення разом із демографічними даними. Результати засвідчили, що свідомий контроль у цієї групи осіб відіграє ключову роль під час психологічної інтервенції. Крім того, автори обговорюють головні нейропсихолінгвістичні принципи, що сприяють вико-ристанню потенціалу свідомого контролю в процесі мовленнєвої реабілітації пацієнтів після інсульту.
Свідомий контроль у мовленнєвій патології та мовленнєвій реабілітації після інсульту
Keywords: stroke; Broca’s aphasia; conscious control; speech pathology; speech rehabilitation; neuropsycholinguistic principles; інсульт; афазія Брока; свідомий контроль; мовленнєва патологія; мовленнєва реабілітація; нейропсихолінгвістичні принципи